Long-Term Effect of Early Post-operative Transcutaneous Electrical Stimulation on Voiding Function After Radical Hysterectomy: A Multicenter, Randomized, Controlled Trial - Li, Xiao-wei; Gao, Lei; Wang, Qing; Lv, Qiu-bo; Xia, Zhi-jun; Wen, Hong-wu; Han, Jin-song; Wu, Yu-mei; Wang, Su-mei; Liu, Qing; Li, Huan; Wang, Hai-bo; et al. (Frontiers in Medicine, 2021)
Introduction: Post-radical-hysterectomy (RH) patients suffer from a series of problems resulted from neurovascular injury, such as bladder dysfunction, that reduces the quality of their life. We design this study to evaluate the efficacy of transcutaneous electrical stimulation (TENS) on patient rehabilitation after RH for early cervical cancer. Materials and Methods: 97patients were enrolled in a randomized-controlled trial (January 2015-December 2019) involving7 medical centers nation-wide. Patients were armed as intervention group (n = 46) and control group (n = 51). TENS were given to patients in intervention group from the 7th day after surgeryfor a total of 14-21days. Control group received no TENS. Primary outcomes were measured for residual urine volume and improvement rate of urination. Secondary outcomes were measures for urodynamics (UDS) , pelvic floor electromyography function examination (PFEmF) and quality of life(QoL). Results: Residual urine volume and improvement rate of urination were found no significant differences in the 14th, 21st, and 28th days after surgery. The maximum flow rate (Qmax) in intervention group was significantly higher than that in control group in the 28thday, but there were no significant differences in average flow rate, voiding time, time to Qmax, muscle fiber strength, muscle fibers fatigue and the abnormal rate of A3 reflection in the 28thday and the 3rdmo, as well as in the QoL at 3rdmo,6thmo, and 12thmo after surgery. Conclusion: Our study showed no sufficient evidence to prove that TENS under the trialed parameters could improve the subject's voiding function, PFEmF, and QOL after RH which had provided valuable data for the rehabilitation after RH.